2020
DOI: 10.15294/jne.v6i1.24170
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Work Environment and Work Motivation in Influencing the Performance of Non-Formal Educators

Abstract: Work Environment and Work Motivation can affect performance in an institution, institution or company. For that, a leader needs to think about it. The purpose of this study was to determine: (1) the influence of the work environment with the performance of Non-formal Educators on the Development Center for Early Childhood Education and Gorontalo Community Education, (2) the effect of work motivation on the performance of Non-Formal Educators at the Center for Early Childhood Education Development and Gorontalo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
2
0
1
Order By: Relevance
“…That is, the better the work environment owned by the organization, the better the work results shown. Thus, this finding strengthens previous research and is supported by several facts and empirical data which state that the work environment in the form of a work atmosphere, relationships with colleagues, the availability of work facilities affect performance (Djibu & Duludu, 2020;Hannif et al, 2014). The work environment is one of the factors that affect the performance of an employee.…”
Section: Discussionsupporting
confidence: 88%
“…That is, the better the work environment owned by the organization, the better the work results shown. Thus, this finding strengthens previous research and is supported by several facts and empirical data which state that the work environment in the form of a work atmosphere, relationships with colleagues, the availability of work facilities affect performance (Djibu & Duludu, 2020;Hannif et al, 2014). The work environment is one of the factors that affect the performance of an employee.…”
Section: Discussionsupporting
confidence: 88%
“…According to (Djibu & Duludu, 2020) states that: Curriculum development based on management, means carrying out curriculum development activities based on a management mindset, or based on management processes according to management functions. The series of curriculum management processes in educational institutions covers the areas of planning, organizing and coordinating, implementing, and evaluating/supervising.…”
Section: Ppsdp International Journal Of Educationmentioning
confidence: 99%
“…According to Enny (2019, pp.57), a conducive work environment in the workplace is one of the requirements to create better change performance. (Wulandari et al, 2021;Dafruddin & Heryanto, 2019: Djibu & Duludu, 2020 found that a good work environment will improve performance, so based on that hypothesis 1 was formulated that the work environment affects employee performance. Better leadership implementation will optimize employee performance (Widyaningrum, 2020).…”
Section: Hypothesismentioning
confidence: 99%